MRI and dental implantology: Two which do not exclude each other. (June 2015) - Korn, P.; Elschner, C.; Schulz, M.C.; Range, U.; Mai, R.; Scheler, U.
Abstract: Currently, histological techniques are used to analyse implant-tissue-interactions. However, these methods are destructive and time-consuming. Furthermore, they require a large number of animals as longitudinal observations in one individual are not possible. The evaluation by non-destructive imaging techniques provides the opportunity to study the osseous integration with a reduced number of animals and a decreased biological variability. The present study examined the suitability of magnetic resonance imaging (MRI) to assess peri-implant bone formation exemplarily for a dental implant in a minipig model. Due to its compatibility to MR imaging polyetheretherketone (PEEK) coated with a thin layer of titanium was applied as implant material. Osseointegration was analysed within different peri-implant regions quantifying bone volume density and soft tissue content, which were assessed by MRI and histology, likewise. It could be proven that the examined regions showed differences in bone formation; the region adjacent to the implant apex turned out to be the most dynamic. Both methods led to comparable results with no significant differences regarding to the assessed parameters. Moreover, it was demonstrated that titanium coated PEEK showed a sufficient osseointegration and MRI provides a promising application in monitoring bone formation.